Inhibitory activity restricts the function of an avian-like influenza polymerase in primate cells - Mehle, Andrew (2008)
Transmission of highly pathogenic avian influenza across species into human populations can result in lethal infections and increases the potential of a pandemic outbreak. A major determinant of species tropism is the influenza polymerase subunit PB2. We show here that a dominant inhibitory activity in human cells potently and selectively restricts the function of polymerase containing an avian-like PB2 with glutamic acid at residue 627. This inhibitory activity dramatically reduces virus production by polymerases containing PB2 K627E without reducing their relative infectivity. Restricted polymerases fail to assemble into ribonucleoprotein complexes, resulting in decreased genome transcription, replication, and virus production. However, both wild-type and mutant PB2 bind to viral nucleoprotein when expressed alone, suggesting that species-specific conformational alterations within the polymerase trimer disrupt ribonucleoprotein assembly. Understanding the molecular basis for influenza virus host cell specificity and pathogenesis will enable rational strategies to treat and prevent future avian influenza outbreaks in humans.